Implementation Of Regional Property Management Regulations In The Management Of Regional Property Input Grants In The Health Office Of Southeast Minahasa Regency - Landy L.A. Pesik; Wilson Bogar; Meidy S.S. Kantohe (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the implementation of the Minister of Home Affairs Regulation (Permendagri) Number 7 of 2024 concerning the Management of Regional Government-Owned Assets (BMD) in managing incoming grants of regional assets at the Health Office of Southeast Minahasa Regency. The focus of this research includes the apparatus's understanding of the regulation, planning for grant management, the execution of incoming grant management, as well as the obstacles and impacts of policy implementation. This study employed a descriptive qualitative approach, with data collection techniques including in-depth interviews, observation, and documentation. The research informants were selected using purposive sampling, consisting of 5 personnel from the Regional Financial and Revenue Management Agency and the Health Office of Southeast Minahasa Regency. The results indicate that the implementation of Permendagri Number 7 of 2024 has not been optimal. The apparatus's understanding remains limited to a basic level, grant planning has not been integrated into the Regional Asset Needs Planning (RKBMD) document, and the execution of grants does not fully comply with procedures due to incomplete administrative documentation. Furthermore, the main obstacles include limited human resources, weak inter-agency coordination, and administrative disorder. This study recommends continuous socialization of the regulation, the provision of technical guidance, the integration of grants into planning documents, and enhanced coordination among relevant parties. Keywords: Policy Implementation, Incoming Grants, Regional Government-Owned Assets, Health Office, Permendagri Number 7 of 2024.